2015
DOI: 10.2514/1.b34804
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis and Design for Embedded Engine Inlets

Abstract: The present paper demonstrates the aerodynamic feasibility of boundary-layer ingesting embedded-engine inlet designs with low total pressure losses and distortion harmonic content. The inlet was designed using a hierarchical multi-objective computational fluid dynamics optimization that combined global and local shaping. Global parameters including duct offset and length, wall curvature and shape, inlet aspect ratio, lip contour and thickness, and upstream airframe contour were used to identify optimal design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Mesh-based distortion elements were employed to create profiles of total pressure which are representative of an approaching boundary layer. Studies of typical boundary layer ingestion airframe configurations reveal that the thickness of the boundary layer at the inlet plane of a rear-mounted intake is expected to be approximately 0.3Hin [7], but may reach as much as 0.6Hin depending on the engine placement [15]. This is of significance as the distributions of total pressure loss at the AIP are sensitive to the thickness of the approaching boundary layer [15].…”
Section: E Distortion Screens and Test Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesh-based distortion elements were employed to create profiles of total pressure which are representative of an approaching boundary layer. Studies of typical boundary layer ingestion airframe configurations reveal that the thickness of the boundary layer at the inlet plane of a rear-mounted intake is expected to be approximately 0.3Hin [7], but may reach as much as 0.6Hin depending on the engine placement [15]. This is of significance as the distributions of total pressure loss at the AIP are sensitive to the thickness of the approaching boundary layer [15].…”
Section: E Distortion Screens and Test Matrixmentioning
confidence: 99%
“…The flow distortion can be highly dynamic [2][3][4] [5] and has the potential to adversely influence the stability and operability of the engine [6][7] [8]. Studies have demonstrated that the levels of intake flow distortion can be reduced by redesign of the intake geometry [7], or the use of flow control [9] [10]. However, as the flow distortion cannot be removed completely, it is necessary to develop turbomachinery designs which are tolerant to continuous operation in distorted flow.…”
Section: Iintroductionmentioning
confidence: 99%
“…It is expected that future aircraft configurations will require more closely coupled propulsion and airframe architectures (Kawai et al 2006;Kim and Liou 2013;Florea et al 2015;Gan and Zhang 2017) which often feature convoluted intakes to deliver the air flow to the engine. Although such aircraft configurations may allow for weight and drag benefits, the coupling between the intake and engine compression system becomes more critical.…”
Section: Introductionmentioning
confidence: 99%
“…There has been recent computational work on BLI fan stage performance, including description of the design of a distortiontolerant BLI fan stage, with estimates of reductions in stage efficiency of 1-2% relative to uniform flow [12]. Other computational and experimental analyses have found similar efficiency reductions for different geometries [13,14].…”
Section: Introductionmentioning
confidence: 99%